Failure analysis of a machine support for fique fibre processing. (October 2015) - Delgado, F.; Coronado, J.J.; Rodríguez, S.A.
Highlights: Cast steel supports have presented recurrent fracture beyond 10 6 cycles of service. Evidence of fatigue in alternating bending condition was observed. Differences between original supports and replacement supports were identified. Modifications of the geometry and use of different material were proposed. Abstract: Replacement cast steel supports for a machine consisting of bars that straighten out fique fibres have presented recurrent fracture, beyond 10 6 cycles of service and their failure surfaces show features typical of fatigue under alternating bending conditions. Differences between original supports and replacement supports related to geometry roughness, hardness, chemical composition and microstructure were identified. To obtain a longer service life selected modifications of the geometry and use of different material were proposed based on load state analysis, finite element analysis, and fatigue strength calculations.